Utilization of by-products and Cleaner Production in industrial Nile perch processing in Kenya - Wairangu, Ephraim; Kitur, Esther; Macharia, Geoffrey (International Journal of Environmental Sciences, 2016)
Purpose: The Lake Victorian Nile Perch (Lates niloticus) industry in Kenya is the most important in the fisheries sub-sector and generates significant levels of revenue to the national economy besides creating employment opportunities along the value chain. Information on the utilization of by-products and cleaner production is very important as the industry plays a significant role in the economic and social development in the country. The main products from processing are chilled or frozen Nile perch (NP) fillets exclusively destined for the export market. The processing further produces vast amounts of waste water. Methodology: NP by-products and CP were audited by surveying three NP processing plants in Nairobi, Homa Bay and Kisumu. The three fish processing plants were purposively selected. Simple random sampling technique was used to select respondents as it presented every potential respondent an equal chance of being selected to take part in the study without bias. A sample of 139 was used. Structured questionnaire, structured interview schedules and observation checklists were used as research instruments. Data was analyzed using Statistical Package for Social Sciences (SPSS). Results: There has been an increasing interest in Nile perch by-products over the past two decades. Various factors were tested to have negative significant association with utilization of by products that included lack of expertise with a correlation of -0.716, lack of appropriate technologies with -0.874, financial constraints with -0.624, lack of markets, -0.559, lack of raw materials with -0.547 and poor management practices with -0.738 correlation coefficient. The results of this study indicated that there were several by-products and these included fish maws, fish frames, skins, scales, viscera, fish pads and proteinous thick liquid. Cleaner Production (CP) employed by the Nile Perch processing plants was to a large extent covered by the fisheries regulations, company policies, Hazard Analysis Critical Control Point (HACCP), Sanitation Standard Operating Procedures (SSOP) and Good Manufacturing Practices (GMP) which were documented in various manuals. Recommendation: The government in consultation with the industry should develop and implement appropriate policies that govern the utilization of the by-products. There is need to build capacity on the part of the management and the employees on the principles and implementation of CP. Through this, the NP management needs to fully align CP with the documented HACCP and SSOP manuals that are currently in place in all the NP processing plants. There is a need to find appropriate ways of reducing water and energy usage as well as minimize the amount of waste released into the environment in order to avoid the negative consequences.